Effect of Textile Effluent on Dry Matter Yield and Nutrient Content Of Jute Leaves (Corchorus Capsularis) (Journal of Biodiversity Conservation and Bioresource Management, 2022)
A pot experiment was conducted at Bangladesh Jute Research Institute (BJRI) to evaluate the effect of textile effluent on dry matter yield and the nutrients content of newly developed BJRI Deshi pat shak-1 (Corchorus capsularis). The treatments were T1: control, T2: 100% RDF + 0% effluent, T3: 50% RDF + 25% effluent, T4: 50% RDF +50% effluent, T5: 50% RDF + 75% effluent, T6: 50% RDF + 100% effluent. All the treatments had significant positive effect over control on dry matter yield and nutrient content of jute vegetables on non-contaminated soils. But in contaminated soils effluent irrigation showed negative effect on dry matter yield and nutrient content of jute leaves vegetables over control. The highest yield of dry matter in both contaminated and non-contaminated soils were observed in treatment T2 (100% RDF + 0% effluent), which were1.81, 1.90, 1.86 and 1.69 t/ha in non-contaminated and contaminated soils of Narayanganj and Gazipur, respectively. Among the textile effluent treated pots T4 the gave second highest yield of dry matter yield which were 1.55, 1.77, 1.36 and 1.58 t/ha in non- contaminated and contaminated soils, respectively.J. Biodivers. Conserv. Bioresour. Manag. 2021, 7(2): 47-54